Managing Pharmaceutical Costs in Health Systems: A Review of Affordability, Accessibility and Sustainability Strategies - Christos Ntais; Michael A. Talias; John Fanourgiakis; Nikolaos Kontodimopoulos (Journal of Market Access & Health Policy)
Background: This paper reviews cost containment policies to control pharmaceutical expenditure either by regulating the pharmaceutical industry or targeting the demand side. Methods: The method used was the narrative literature review of studies which assessed the effect of pharmaceutical cost containment policies. Results: Governments worldwide have implemented a great variety of policy measures to manage pharmaceutical expenditure while ensuring fair access to essential medicines. Cost-sharing schemes, value-based pricing, reimbursement, reference pricing, payback mechanisms and the substitution of original drugs with generics and biosimilars are pivotal in these efforts, albeit with differing effectiveness across healthcare systems. Overall, it appears that any gains may be outweighed by the unfavorable effects of policies impacting patients. Although interventions have been created to improve physicians’ prescribing practice, they often achieve very minor benefits and at considerable cost. Policy measures pertaining to the regulation of the supply side must be supported by thorough evaluation in order to ascertain costs and effects and guarantee that unintended consequences are minimized. Conclusions: Policymakers frequently enact numerous laws and regulations to control pharmaceutical expenditure, even if there is limited evidence that they are cost-effective. The most crucial component of any policy’s success, regardless of the one selected, is its evaluation. Further research is needed to develop context-specific guidance that balances cost containment, equity and sustainability.